2022
DOI: 10.3390/nano12020255
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Covalent Triazine Framework Functional Interlayer for High-Performance Lithium–Sulfur Batteries

Abstract: The shuttling effect of polysulfides is one of the major problems of lithium–sulfur (Li–S) batteries, which causes rapid capacity fading during cycling. Modification of the commercial separator with a functional interlayer is an effective strategy to address this issue. Herein, we modified the commercial Celgard separator of Li–S batteries with one-dimensional (1D) covalent triazine framework (CTF) and a carbon nanotube (CNT) composite as a functional interlayer. The intertwined CTF/CNT can provide a fast lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…[79] For instance, Hu et.al prepared a CTF/CNT-modified Celgard separator through vacuum filtration for high-density Lithium-sulfur batteries. [80] The thickness and loading mass of the coating layer can be adjusted by the amount of CTE, CNT, and PVDF. Similarly, Tian et al obtained a MOF separator that is ultrathin, highly-orientated, and flexible via vacuum filtration (Figure 2b) of the Cu 2 (CuTCPP) nanosheet suspension.…”
Section: Vacuum Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] For instance, Hu et.al prepared a CTF/CNT-modified Celgard separator through vacuum filtration for high-density Lithium-sulfur batteries. [80] The thickness and loading mass of the coating layer can be adjusted by the amount of CTE, CNT, and PVDF. Similarly, Tian et al obtained a MOF separator that is ultrathin, highly-orientated, and flexible via vacuum filtration (Figure 2b) of the Cu 2 (CuTCPP) nanosheet suspension.…”
Section: Vacuum Filtrationmentioning
confidence: 99%
“…Previous studies have shown that this method is simple, convenient and scalable, which is beneficial to the synthesis of modified separators [79] . For instance, Hu et.al prepared a CTF/CNT‐modified Celgard separator through vacuum filtration for high‐density Lithium‐sulfur batteries [80] . The thickness and loading mass of the coating layer can be adjusted by the amount of CTE, CNT, and PVDF.…”
Section: Fabrication Of Mofs/cofs Based Separatorsmentioning
confidence: 99%
“…Subsequently, Zhang et al modified the general Li–S battery separator using a CTF‐type COF. [ 69 ] The CTF/CNT composite could offer a regular channel for quick Li + /electronic transport and exhibits potent PSs‐adsorption properties. Using the CTF/CNT/Celgard separator, the rate capability and cycle properties of the battery are obviously promoted.…”
Section: Application Of Cofs In S‐based Battery Separatorsmentioning
confidence: 99%